An Analysis of Hegemonic Competition between the United States and China - Md. Riyad Siddiquei; Md Ikhtiar Uddin Bhuiyan (Asian Studies, 2024)
International relations theory plays a role in understanding national behavior and sometimes fails to play a role due to ideological misunderstandings. This study explores the hegemonic competition between the United States and China using secondary data. 50% of commercial containers pass through the Taiwan Strait every day. Taiwan produces 70% of the total computer chip exports. The Indo-Pacific region is the world’s largest energy supply chain and trade supply chain. China’s recently announced restrictions on exports of two key semiconductor manufacturing components are about to come into effect. A new executive order signed by US President Joe Biden will ban US investment in China’s key technology sectors. Through this, the US wants to create obstacles in China’s military sector and technology sector. This essay reflects that constructivism and realism can interact rather than oppose each other to better understand behavior among states. Because constructivism can play a complementary role to realism. This combination can promote relations of understanding between states without compromising the interests of states to reduce the likelihood of conflict and war. Finally, the involvement of ideology is reflected in the ups and downs of Sino-US relations. In other words, this method has its basis in analyzing the current relationship between China and America. It is realized that in this method two countries can avoid war between them.